Infection control strategies for healthcare workers during COVID-19 pandemic in German hospitals: A cross-sectional study in march–april 2021. Issue 3 (March 2023) - Mardiko, Amelia A.; Bludau, Anna; Heinemann, Stephanie; Kaba, Hani E.J.; Fenz, Diana; Leha, Andreas; von Maltzahn, Nicole; Mutters, Nico T.; Leistner, Rasmus; Mattner, Frauke; Scheithauer, Simone
Abstract: Background: Healthcare workers (HCW) are at risk of getting infected with COVID-19 at work. To prevent such incidents and provide a safe environment in hospitals, comprehensive infection control strategies are necessary. We aimed to collect information on COVID-19 infection control strategies regarding personal protective equipment (PPE), regulations during breaks for HCW and dissemination of pandemic-related information. Methods: We invited infection control practitioners from 987 randomly selected German hospitals in March–April 2021 to participate in our cross-sectional online survey. We categorized the hospital based on bed capacity (≤499 beds = small; ≥500 beds = large). Fisher's exact test was performed and p < 0.05 defined as statistically significant. Findings: 100 participants completed the questionnaire. Small hospitals were more directive about requiring FFP2 respirators (63%), whereas larger hospitals more often gave their HCW a choice between these and medical masks (67%). For the care of COVID-19 and suspected COVID-19 cases, >90% of the participants recommended the use of gloves. Notably, gloves were recommended beyond COVID-19 in 30% of the hospitals. During meal breaks various strategies were followed. Conclusion: Recommendations for PPE varied across hospital sizes, which could be due to different assessments of necessity and safety. Regulations during breaks varied strongly which illustrates the need for clear official guidelines. Highlights: Recommendations for PPE varied across hospital sizes. >90% of hospitals recommended glove use for COVID-19 patients; 30% in general. Small hospitals were more directive about requiring FFP2 respirators. Most hospitals restricted the number of employees in the room during lunch breaks. Physical distance was confirmed as infection control strategy during cigarette breaks.